STRATEGI PEMASARAN DIMSUM KIANO DALAM MEMPENGARUHI KEPUTUSAN PEMBELIAN MASYARAKAT DIKOTA RANTAU PRAPAT - Andini, Ratih; Simanjorang, Elida Florentina Sinaga; Ritonga, Mulkan (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
To determine the target market and meet consumer needs by combining the marketing mix, companies use marketing strategies as an overall program. The purpose of this study is to determine how Dimsum Kiano's marketing strategy influences people's decisions to buy the product. This research utilizes a qualitative descriptive approach. Data was collected through direct observations and interviews with respondents who have been determined and also documentation techniques. The data obtained from the sources were examined for data reduction, then the data were analyzed and presented, then made conclusions. The results showed that the main strength of the dimsum marketing strategy is maintaining good product quality so that people are interested and get more enthusiasts. The main weakness of this strategy is less effective promotional activities, which threaten more creative competitors.